In situ atomic‐scale observation of size‐dependent (de)potassiation and reversible phase transformation in tetragonal FeSe anodes. Issue 1 (8th September 2022) - Cai, Ran; Bao, Lixia; Zhang, Wenqi; Xia, Weiwei; Sun, Chunhao; Dong, Weikang; Chang, Xiaoxue; Hua, Ze; Shao, Ruiwen; Fukuda, Toshio; Sun, Zhefei; Liu, Haodong; et al.
Abstract: Potassium‐ion batteries (PIBs) are considered promising alternatives to lithium‐ion batteries owing to cost‐effective potassium resources and a suitable redox potential of −2.93 V (vs. −3.04 V for Li + /Li). However, the exploration of appropriate electrode materials with the correct size for reversibly accommodating large K + ions presents a significant challenge. In addition, the reaction mechanisms and origins of enhanced performance remain elusive. Here, tetragonal FeSe nanoflakes of different sizes are designed to serve as an anode for PIBs, and their live and atomic‐scale potassiation/depotassiation mechanisms are revealed for the first time through in situ high‐resolution transmission electron microscopy. We found that FeSe undergoes two distinct structural evolutions, sequentially characterized by intercalation and conversion reactions, and the initial intercalation behavior is size‐dependent. Apparent expansion induced by the intercalation of K + ions is observed in small‐sized FeSe nanoflakes, whereas unexpected cracks are formed along the direction of ionic diffusion in large‐sized nanoflakes. The significant stress generation and crack extension originating from the combined effect of mechanical and electrochemical interactions are elucidated by geometric phase analysis and finite‐element analysis. Despite the different intercalation behaviors, the formed products of Fe and K2 Se after full potassiation can be converted back into the original FeSe phase upon depotassiation. In particular, small‐sized nanoflakes exhibit better cycling performance with well‐maintained structural integrity. This article presents the first successful demonstration of atomic‐scale visualization that can reveal size‐dependent potassiation dynamics. Moreover, it provides valuable guidelines for optimizing the dimensions of electrode materials for advanced PIBs. Abstract : The tetragonal FeSe nanoflakes with different sizes are designed and their atomic‐scale potassiation/depotassiation mechanisms are revealed for the first time through in situ high‐resolution transmission electron microscopy. FeSe undergoes two distinct structural evolutions, sequentially characterized by intercalation and conversion reactions, and the initial intercalation behavior is size‐dependent originating from the combined effect of the mechanical and electrochemical interaction.